eSport in Recht und Gesellschaft - Seckelmann, Margrit; Woerleiin, Andreas H. (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The conference volume of the Competence Center eSport of Leibniz Universität Hannover contains, in addition to the introductory preface and annual report, a total of thirteen contributions on the legal and sociological implementation of eSports. The legal focus of the first conference volume reflects the character of eSports law as a cross-sectional subject. In addition to contributions on the (legal) political classification, data protection and labor law in eSports, a classification of eSports betting and lootboxes in terms of gambling law is also provided. In addition, the phenomenon of NFTs as well as blockchain technology is extensively addressed. Finally, further practical legal research is followed by an analysis of the platformization of the eSports ecosystem as well as eSports at national universities. With contributions byLuis Blödorn | Carl Cevin-Key Coste, LL.B. | Jasmin Dolling, LL.B. | Adrian Fischer, LL.M. | RA Kai Korte | RAin Marisa Machacek LL.M. (UCL) | Lina Marquard, LL.B. | RAin Ann-Marie Sahm, Mag. iur. | Dr. Tobias M. Scholz | Prof. Dr. Margrit Seckelmann, M.A. | Patrick Semrau | Nicolas Thöne, LL.M. | Fabian Will, Mag. iur. | RA Dr. Andreas H. Woerlein, LL.M. | Dr. Anton Zimmermann